New Improvements of the Jensen–Mercer Inequality for Strongly Convex Functions with Applications - Adil Khan, Muhammad; Ivelić Bradanović, Slavica; Mahmoud, Haitham Abbas (Axioms, 2024)
In this paper, we use the generalized version of convex functions, known as strongly convex functions, to derive improvements to the Jensen–Mercer inequality. We achieve these improvements through the newly discovered characterizations of strongly convex functions, along with some previously known results about strongly convex functions. We are also focused on important applications of the derived results in information theory, deducing estimates for χ-divergence, Kullback–Leibler divergence, Hellinger distance, Bhattacharya distance, Jeffreys distance, and Jensen–Shannon divergence. Additionally, we prove some applications to Mercer-type power means at the end.